The Border reader - Loza, Mireya; Rosas, Gilberto, 1968- (Duke University Press, 2023)
"The Border Reader is an anthology which gathers previously published foundational works of humanities and interpretive social science scholarship on the U.S.-Mexico border. Edited by anthropologist Gilberto Rosas and American and Latinx studies scholar Mireya Roza, this Reader brings together essays that mobilize feminist, queer, Indigenous and critical ethnic studies perspectives to theorize the border region as a site of epistemic rupture and knowledge production"--